Anesthesia and rare neuromuscular diseases - Radeka, Jovan Z.; Stojanovic, Milena Dragisa; Vasilijic, Milena N.; Randjelovic, Milica Miroslav; Jankovic, Radmilo J. (Frontiers in Anesthesiology, 2023)
Neuromuscular diseases, although rare in the general population, can be present in people who need to undergo surgery and anesthesia. Fortunately, the possibility of early diagnosis, new therapeutic approaches and the application of a multidisciplinary approach have significantly extended the life expectancy of such patients. The presence of such a disorder represents a challenge in anesthesiology practice, both during the preparation for surgery itself, the operative procedure and postoperative recovery in intensive care units. A basic understanding of the main disorders of the disease and their potential interactions with the anesthetic itself and the necessary agents in anesthesiology is necessary in order to reduce the risk of perioperative morbidity and mortality, with the aim of reducing the possibility of complications. Rare muscle diseases are very difficult to classify in a standard way because of the variability of their etiology and pathology. This work focuses on a number of muscle diseases such as Dubowitz syndrome, rhabdomyosarcoma in children, spinal muscular atrophy, Kennedy's disease, Congenital muscular dystrophy of the Ullrich type (UCMD), Sotos syndrome, Polymyositis and Setleis syndrome, Nemaline rod myopathy, Pompe disease, Emery-Dreifuss muscular dystrophy (EDMD). The medical literature on anesthetic techniques and perioperative complications was reviewed. Given that they can have a very unfavorable effect on the course of general anesthesia in particular and that these diseases can cause very serious, even life-threatening complications, an adequate anesthesiological approach is very important to reduce the possibility of the mentioned complications. A multidisciplinary approach is imperative for such patients before and after surgery, whether it is performed under analgosedation, some type of regional or general anesthesia. The operative procedure itself must be performed in institutions that are adequately equipped to treat such patients and by personnel who have experience in treating them.